Building Artificial Climates. Thermal control and comfort in Modern Architecture (1930-1960) - Ignacio Requena-Ruiz (Ambiances)
In the mid-twentieth century, the evolution of the various dimensions involved in the notion of climate led to a different vision of the relationship between bodies and indoor atmospheres. This article states that Modern Architecture hosted and promoted this change in cultural representations, social practices and technical developments of temperature and climate in indoor spaces. Our aim is to bring together points of view and interpretations of the cultural history, the history of techniques and the history of sensory perception in order to understand how the climatic dimension of indoor atmospheres became an agent of architectural transformation. In particular, the article focuses like a case study on the collaboration between Le Corbusier and André Missenard, a climate control specialist, through original archival research. As a result, we show how their theoretical reflections and built works illustrate a broader interest in architecture as a way of creating the ideal climates for modern ways of life.